Methicillin-resistant Staphylococcus aureus (MRSA): antibiotic-resistance and the biofilm phenotype - Craft, Kelly M.; Nguyen, Johny M.; Berg, Lawrence J.; Townsend, Steven D. (MedChemComm, 2019)
Staphylococcus aureus ( S. aureus ) is an asymptomatic colonizer of 30% of all human beings. While generally benign, antibiotic resistance contributes to the success of S. aureus as a human pathogen. Resistance is rapidly evolved through a wide portfolio of mechanisms including horizontal gene transfer and chromosomal mutation. In addition to traditional resistance mechanisms, a special feature of S. aureus pathogenesis is its ability to survive on both biotic and abiotic surfaces in the biofilm state. Due to this characteristic, S. aureus is a leading cause of human infection. Methicillin-resistant S. aureus (MRSA) in particular has emerged as a widespread cause of both community- and hospital-acquired infections. Currently, MRSA is responsible for 10-fold more infections than all multi-drug resistant (MDR) Gram-negative pathogens combined. Recently, MRSA was classified by the World Health Organization (WHO) as one of twelve priority pathogens that threaten human health. In this targeted mini-review, we discuss MRSA biofilm production, the relationship of biofilm production to antibiotic resistance, and front-line techniques to defeat the biofilm-resistance system.